2020
DOI: 10.3168/jds.2019-17477
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Investigation of extra-intestinal pathogenic Escherichia coli virulence genes, bacterial motility, and multidrug resistance pattern of strains isolated from dairy cows with different severity scores of clinical mastitis

Abstract: Escherichia coli is a major pathogen involved in the etiology of environmentally derived bovine mastitis and is characterized by a variety of virulence factors (VF). Mammary infections with E. coli have shown a wide range of clinical signs, causing changes in milk (score 1, or mild), abnormal appearance of milk and udder inflammation (score 2, or moderate), and abnormalities in milk, udder inflammation, and systemic signs of illness (score 3, or severe). Nevertheless, to date, the profile of the genes related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
4
24
2
1
Order By: Relevance
“…15.9% and chuA= 8.3%) are situated in the ranges. Nevertheless, presence of fyuA (15.3%) and iroN (14%) among our isolates were higher than previous records (2.5% and 3.5%, respectively) (12,14). Unfortunately, our results of iron acquisition genotypes are incomparable with most of the previous studies, as no focus on iron uptake systems can be observed among them.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…15.9% and chuA= 8.3%) are situated in the ranges. Nevertheless, presence of fyuA (15.3%) and iroN (14%) among our isolates were higher than previous records (2.5% and 3.5%, respectively) (12,14). Unfortunately, our results of iron acquisition genotypes are incomparable with most of the previous studies, as no focus on iron uptake systems can be observed among them.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the data about chuA can be extracted from the results of phylogenetic grouping conducted based on the Clermont’s procedures. Prevalence of the genes iucD, irp2 and chuA are recorded in ranges of 0-16.7% (12, 13), 2.5-26.4% (13, 14) and 5.7-35.6% (15, 16), respectively by other researchers, and our findings ( iucD = 10.8%, irp2 = 15.9% and chuA = 8.3%) are situated in the ranges. Nevertheless, presence of fyuA (15.3%) and iroN (14%) among our isolates were higher than previous records (2.5% and 3.5%, respectively) (12, 14).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The virulome of our colistin-resistant isolates was screened in each species. Many of the identified virulence genes in our study were required for bacterial survival and had a role in causing mastitis ( Tartor and El-Naenaeey, 2016 ; Gao et al., 2019 ; Guerra et al., 2020 ). This in turn raises the alarm that most of the colistin-resistant Gram-negative isolates are highly pathogenic.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, E. coli has become the most important pathogen inducing cow mastitis, mainly causing high fever or lower milk production, even resulting in lethal consequences (Fazel et al, 2019;Guerra et al, 2020). Also, E. coli is an important antibiotic-resistant priority pathogen and can disseminate resistant genes in a process known as 'horizontal transfer' into other microbial communities (Jianying et al, 2008).…”
Section: Discussionmentioning
confidence: 99%